CULTURAL INTERMEDIATION AT THE INTERSECTION POINT OF INSTITUTIONAL CO-CREATION: RECONFIGURING PARTICIPATION WITHIN THE AUSTRALIAN BROADCASTING CORPORATION (ABC) - Hutchinson, Jonathon (AoIR Selected Papers of Internet Research, 2014)
These data emerge from a three-year research project that used an ethnographic action research methodology where I was embedded as the community manager of ABC Pool. Participant observation was the core method of my online ethnography, referred to by Bowler (2010) as netnography and defined as research that explores the “cultural analysis and representation, from the observation of co- located, face-to-face interactions to technologically mediated interactions in online networks and communities, and the culture (or cyberculture) shared between and among them” (Bowler, 2010, p. 1271). The action method aligned with my community manager role, defined as “integrating your research into the development of your project” (Tacchi, Slater & Hearn, 2003, p. 12). Additional data was found through surveys, focus groups, semi-structured interviews and textual analysis. This paper draws on a case study of the New Beginnings project, which is a 53-minute co-creative documentary, produced through ABC Pool and broadcast on Radio National’s 360documentaries.